ANALISIS EFEK PERTUMBUHAN EKONOMI PADA DISTRIBUSI PENDAPATAN DI KABUPATEN JOMBANG - Anang Rahmat Jatmiko (eBA Journal: Journal Economic, Bussines dan Accounting, 2014)
The Jombang Regency is one of Regency that achieves a rapids economics grotwh. Its can be show in the increase of Growth Domestic Regional Product (GDRP) of Jombang Regency. Economics Growth, however, may cause a chane of income distribution. The purpose of this analysis is to find the correlaton between economics growth and the rate of inequality of income distribution in Jombang Regency trhough statistical test. This is based on data of GDRP and the measure of Gini Ratio Index of Jombang Regency during period 2005-2013. And the Ordinary Least Square Methode is used to find the relationship between the variables. The result shows that there is negative correlation between economics growth and the inequality of income distribution growth in Jombang Regency.